2022
DOI: 10.21837/pm.v20i20.1078
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Current Risk Management Process Practice in Malaysian Landscape Planning Projects

Abstract: The Malaysian landscape planning projects are dynamic, subjective, and fasttracked, causing multiple risks. Hence, risk management practice is needed to manage risks. However, the risk management process is not managed comprehensively despite the considerable capability of project practitioners to predict, analyse, and treat project risks, causing the project to underperform. This study has investigated the current risk management process in Malaysian landscape planning projects. Data were gathered through sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Construction workers can control their conduct to reduce the likelihood of accidents at the site by following safety procedures. Muthuveeran et al (2022) stated that risk assessment can guarantee a distinct risk context for project management procedures. This could assist in enhancing the management of safety procedures on construction sites.…”
Section: Discussionmentioning
confidence: 99%
“…Construction workers can control their conduct to reduce the likelihood of accidents at the site by following safety procedures. Muthuveeran et al (2022) stated that risk assessment can guarantee a distinct risk context for project management procedures. This could assist in enhancing the management of safety procedures on construction sites.…”
Section: Discussionmentioning
confidence: 99%
“…[36] pointed out the use of simple techniques and old tools to identify, analyse, and control risks within Malaysian construction projects, and this relative decline in risk management practices results from a lack of sufficient knowledge of risk management methods. [37] explained that there is a requirement to execute risk management in construction projects in Malaysia because these projects have many risks, and this industry has a dynamic and complex nature.…”
Section: Risk Management In the Malaysian Construction Industrymentioning
confidence: 99%
“…One study found that the lack of the rules and regulations of SIA is the most inconvenient and not effective due to methodological inadequacy (Khan, 2020;Martinez & Komendantova, 2020). Similar to the risk assessment, due to a lack of information and awareness, the SIA is not extensively used as part of the assessment (Muthuveeran et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%